Cold victory eaudiobook A novel. - Marlantes, Karl (Blackstone Publishing, 2024)
From New York Times bestselling author Karl Marlantes comes a propulsive and sweeping novel in which loyalty, friendship, and love are put to the ultimate test. Helsinki, 1947. Finland teeters between the Soviet Union and the West. Everyone is being watched. A wrong look or a wrong word could end in catastrophe. Natalya Bobrova, from Russia, and Louise Koski, from the United States, are young wives of their country's military attachés. When they meet at an embassy party, their husbands, Arnie and Mikhail, both world-class skiers, drunkenly challenge each other to a friendly—but secret—cross-country wilderness race. This is another masterful novel from the author of the modern classic Matterhorn, whose "breakneck writing style is both passionate and haunting" (W. E. B. Griffin). Layered with fast-paced action, historical detail, and a keen eye for the way totalitarianism and loss of truth and privacy threatens love and friendship, Cold Victory is a triumph.